Multi-agent framework for negotiation in a closed environment - Cretan, A.; Coutinho, C.; Bratu, B.; Jardim-Goncalves, R. (Proceedings of the 11th International Conference of Numerical Analysis and Applied Mathematics (ICNAAM 2013), 2013)
The goal of this paper is to offer support for small and medium enterprises which cannot or do not want to fulfil a big contract alone. Each organization has limited resources and in order to better accomplish a higher external demand, the managers are forced to outsource parts of their contracts even to concurrent organizations. In this concurrent environment each enterprise wants to preserve its decision autonomy and to disclose as little as possible from its business information. To describe this interaction, our approach is to define a framework for managing parallel and concurrent negotiations among independent organizations acting in the same industrial market. The complexity of our negotiation framework is done by the dynamic environment in which multi-attribute and multi-participant negotiations are racing over the same set of resources. Moreover, the proposed framework helps the organizations within the collaborative networked environment to augment their efficiency and ability to react to unforeseen situations, thus improving their market competitiveness.